2014
DOI: 10.1186/s13568-014-0029-8
|View full text |Cite
|
Sign up to set email alerts
|

Mushroom as a product and their role in mycoremediation

Abstract: Mushroom has been used for consumption as product for a long time due to their flavor and richness in protein. Mushrooms are also known as mycoremediation tool because of their use in remediation of different types of pollutants. Mycoremediation relies on the efficient enzymes, produced by mushroom, for the degradation of various types of substrate and pollutants. Besides waste degradation, mushroom produced a vendible product for consumption. However, sometimes they absorb the pollutant in their mycelium (bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(80 citation statements)
references
References 41 publications
1
71
0
8
Order By: Relevance
“…at Fukushima). It has been suggested that edible mushrooms might be grown for the purposes of mycoremediation, and the prospects of whether they would be safe to eat afterwards are considered (Kulshreshtha et al, 2014). Naturally this depends on the exact nature of the pollutants, so that heavy metals are likely be a problem (if they are absorbed and concentrated into the mushroom), while some organic soil contaminants might be decomposed without so imparting toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…at Fukushima). It has been suggested that edible mushrooms might be grown for the purposes of mycoremediation, and the prospects of whether they would be safe to eat afterwards are considered (Kulshreshtha et al, 2014). Naturally this depends on the exact nature of the pollutants, so that heavy metals are likely be a problem (if they are absorbed and concentrated into the mushroom), while some organic soil contaminants might be decomposed without so imparting toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding to mycoremediation, it is an innovative biotechnological application that uses living fungi for in situ and ex situ clean-up and management of contaminated sites, since they play a broad variety of functions in ecosystem, breaking down long chain pollutants, natural or xenobiotic, into simpler less toxic chemicals and/or removing metals, metalloids and radionuclides (either by adsorption, chemical modification or by influencing chemical bioavailability) from soil and effluents. 127 Especially fungi that are autochthonous for particular sites are effective as bioremediators, 128,129 and their use may be a clean, simple and relatively inexpensive approach that needs only a small space, less skilled persons and can be applied easily in the field for environment correction. 127 A study of the effect of a combined biostimulationbioaugmentation was performed with Rhizopus sp., Penicillium funiculosum and Aspergillus sydowii strains isolated from two aged soils contaminated with 60, 600 and 500,000 mg of a complex mixture of total petroleum hydrocarbons (TPH), which comprises 40% aliphatic hydrocarbons (AH) and 21% polycyclic aromatic hydrocarbons (PAH), per kg −1 dried soil.…”
Section: Mycoremediationmentioning
confidence: 99%
“…127 Especially fungi that are autochthonous for particular sites are effective as bioremediators, 128,129 and their use may be a clean, simple and relatively inexpensive approach that needs only a small space, less skilled persons and can be applied easily in the field for environment correction. 127 A study of the effect of a combined biostimulationbioaugmentation was performed with Rhizopus sp., Penicillium funiculosum and Aspergillus sydowii strains isolated from two aged soils contaminated with 60, 600 and 500,000 mg of a complex mixture of total petroleum hydrocarbons (TPH), which comprises 40% aliphatic hydrocarbons (AH) and 21% polycyclic aromatic hydrocarbons (PAH), per kg −1 dried soil. The native fungi were able to grow in a complex solid mixture of hydrocarbons of high molecular weight, after previous acclimatization in liquid culture, and they removed respectively 36%, 30% and 17% more PAH in comparison with biostimulation alone.…”
Section: Mycoremediationmentioning
confidence: 99%
See 2 more Smart Citations